Geographical Distribution of the Space-Weaving Spider, Chibchea salta, from Northwestern Argentina: New Records and Bioclimatic Modeling - Rubio, Gonzalo Daniel (2011)
New records of the spider Chibchea salta Huber 2000 (Araneae, Pholcidae) from northwestern Argentina are provided, and the potential range of this species is modeled. Two presence-only methods, Maxent and Bioclim, were run using 19 bioclimatic parameters at a resolution of 30 arc seconds. The climatic profile of C. salta is described, and the relative importance of the bioclimatic variables is explored. Temperature variables proved to be more decisive to the final range shape. The range predicted with Maxent is slightly larger than with Bioclim, but the latter appears to be more sensitive to the record set bias. Both methods performed well, resulting in predictive ranges consistent with the yungas ecoregion. These results provide an initial insight into the bioclimatic tolerance of C. salta, and by identifying potential areas with no records, such as the sierras on the Salta-Jujuy border, they also help in identifying sites for future sampling efforts.